2014
DOI: 10.1093/czoolo/60.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic enzymes in seasonally acclimatized and cold acclimated rufous-collared sparrow inhabiting a Chilean Mediterranean environment

Abstract: Due to the higher energy requirements of birds during winter, it is predicted that the activities of metabolic enzymes (e.g., citrate synthase, CS and cytochrome C oxidase, COX) should increase in tandem with increases in rates of energy expenditure (e.g., basal metabolic rate, BMR). However, there is mixed support for the hypothesis of enzymatic acclimatization. Furthermore, there is little information about the effect of ambient temperature on energetics and tissue enzyme activity levels in passerines inhabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 85 publications
4
15
0
Order By: Relevance
“…A reduction in the muscle function could have many effects, taking into consideration that in birds these tissues are responsible for locomotion and thermoregulation. In line with our results, other studies relating to birds suggest that muscles are an important source of heat in terms of shivering thermogenesis in seasonally acclimatized and cold acclimated birds (Liu et al, 2008; Zheng et al, 2008; Liknes and Swanson, 2011a,b; Swanson and Merkord, 2013; Peña-Villalobos et al, 2014). Therefore, a reduction of this enzymatic activity could have negative consequences in the early development of thermogenic capacity, and therefore survival in wild birds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A reduction in the muscle function could have many effects, taking into consideration that in birds these tissues are responsible for locomotion and thermoregulation. In line with our results, other studies relating to birds suggest that muscles are an important source of heat in terms of shivering thermogenesis in seasonally acclimatized and cold acclimated birds (Liu et al, 2008; Zheng et al, 2008; Liknes and Swanson, 2011a,b; Swanson and Merkord, 2013; Peña-Villalobos et al, 2014). Therefore, a reduction of this enzymatic activity could have negative consequences in the early development of thermogenic capacity, and therefore survival in wild birds.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, some studies have found significant correlations between metabolic rates and metabolic enzyme activities. For instance, Zheng et al (2013) reported that basal metabolic rates and liver and muscle mitochondrial COX activities were positively correlated in Pycnonotus sinensis , and Peña-Villalobos et al (2014) observed a positive correlation between basal metabolic rates and pectoral CS activity in Zonotrichia capensis . In fact, we found that experimentally treated embryos in E20 presented lower enzymatic activities in the skeletal muscles, revealing that oxidative capacity is not a fixed trait throughout development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of temperature effect on the mass of the pectoral muscles was a surprising result given the measured increase in whole-body M sum in cold-acclimated birds. Other cases of un-altered skeletal muscles after exposure to cold have been reported (e.g., Williams and Tieleman 2000;Tieleman et al 2003;Peña-Villalobos et al 2014), but these studies used relatively mild temperatures as their cold treatment (e.g., 157C) and did not include M sum measurements. Nonetheless, similar to our study, American goldfinches (Spinus tristis) showed an increase in M sum (Dawson and Carey 1976) with no associated changes in pectoral muscles (Carey et al 1978), and captive dark-eyed juncos (Junco hyemalis) developed a larger heart and increased their M sum in response to cold without a change in the size of their pectoral muscles (Swanson et al 2014c).…”
Section: Organ Mass and Function In The Context Of Cold Acclimationmentioning
confidence: 99%
“…The physiological mechanisms driving phenotypic flexibility in M sum include adjustments in the mass of the pectoralis muscles and changes in the transport capacities for O 2 and metabolic substrates, whereas seasonal adjustments in BMR reflect changes in organ masses, mass-independent metabolic intensities of spe-cific organs, and the activity levels of metabolic enzymes (Swanson 2010;Peña-Villalobos et al 2014;Petit and Vézina 2014;Zhang et al 2015). Recent studies suggest that the functional link between BMR and M sum is not as clear as one might expect, an idea that is supported by the difference in physiological mechanisms determining flexibility in these variables (Swanson et al 2012;Petit et al 2013;Petit and Vézina 2014).…”
Section: Introductionmentioning
confidence: 99%